Sistem Kendali Pembangkit Listrik Tenaga Surya Skala Laboratorium Berbasis Internet of Things - Aidil, Aidil; Muhammad Syafar, Andi (Jurnal Mosfet, 2025)
The increasing demand for renewable energy requires a more efficient and automatically controlled battery charging system. This study aims to design and implement a battery charging control system in a laboratory-scale Solar Power Plant (SPP) using an Internet of Things (IoT) approach. The main issue addressed is how to design a system architecture capable of automatically controlling battery charging and being monitored remotely through an IoT application. The method used involves an ESP32 microcontroller as the control unit, a voltage sensor to read the battery voltage, and a relay as an actuator to disconnect and connect the charging current. Voltage data and charging status are displayed on an LCD and sent in real-time to the Firebase Realtime Database. The system also records historical charging logs in the form of time, voltage, capacity, and charging status data. Test results show that the system works as designed, disconnecting charging when the voltage reaches 13.8V and reactivating it when the voltage drops to 12.20V. The system demonstrates stable charging and discharging performance, with testing recording an upper voltage threshold of 13.87V and a lower voltage threshold of 12.20V. This research proves that the system can serve as an initial solution in the development of IoT-based renewable energy charging monitoring and control technology